EFEKTIVITAS AKTIVITAS KELOMPOK SOSIAL DALAM MENINGKATKAN PERCEIVED SOCIAL SUPPORT WARGA BINAAN PEMASYARAKATAN - Nabila Adelia Mustajab; Azalia Fitriyani; Imey Nurmila; Roswiyani Roswiyani (Berajah Journal, 2026)
Inmates are vulnerable to a decline in perceived social support due to limited social interaction and reduced contact with family members while serving their sentences. This study aims to examine the effectiveness of group activities in enhancing perceived social support among inmates. The study employed a quasi-experimental one-group pretest–posttest design with 11 participants selected via purposive sampling at the X Correctional Institution . Perceived social support was measured using the Multidimensional Scale of Perceived Social Support (MSPSS), and the intervention consisting of group activities was conducted over five sessions spanning six weeks. Analysis results showed a statistically significant increase in the mean MSPSS score from the pre-test (M = 3.86, SD = 0.67) to the post-test (M = 6.03, SD = 0.15), with all participants shifting to the high support category after the intervention. A Paired Samples t-Test confirmed a statistically significant difference (t(10) = −10.916, p < .001). These findings indicate that group activities are effective in increasing perceived social support and have the potential to be developed as a social support-based psychological counseling strategy in correctional settings.